2021
DOI: 10.3390/ijerph182010936
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Temporal and Spatial Variation Analysis of Extreme Temperature Indices: A Case Study of the Yangtze River Basin

Abstract: Extreme temperature change is one of the most urgent challenges facing our society. In recent years, extreme temperature has exerted a considerable influence on society and the global ecosystem. The Yangtze River Basin is not only an important growth belt of China’s social and economic development, but also the main commodity grain base in China. The purpose of this study is to study the extreme temperature indices in the Yangtze River Basin. In this study, the Mann–Kendall nonparametric test and R/S analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The results show that the warming characteristics along the QTPTC were similar to those in other regions. In the region along the QTPTC, the region of the QTP (Gong et al., 2022), Yangtze River Basin (Shi & Ye, 2021), Finland and Global Land (Irannezhad et al., 2018), the trends of most indices were consistent. Particularly in the QTP (Gong et al., 2022), which covers most areas along the transportation corridor, the trend based on the in situ observed station data was completely consistent with the trend in this study based on the estimated temperature gridded data.…”
Section: Discussionmentioning
confidence: 89%
“…The results show that the warming characteristics along the QTPTC were similar to those in other regions. In the region along the QTPTC, the region of the QTP (Gong et al., 2022), Yangtze River Basin (Shi & Ye, 2021), Finland and Global Land (Irannezhad et al., 2018), the trends of most indices were consistent. Particularly in the QTP (Gong et al., 2022), which covers most areas along the transportation corridor, the trend based on the in situ observed station data was completely consistent with the trend in this study based on the estimated temperature gridded data.…”
Section: Discussionmentioning
confidence: 89%
“…A study on extreme temperature change of the last 110 years in Northeast China suggested that the frequency of cold surge events increased significantly, occurring from the mid-1950s to late-1980s [26]. The extreme low temperatures are closely related to regional warming [27], has exerted a considerable impact on the global ecosystem and economic society [28][29]. Coastal regions are also affected by extreme low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The Yangtze River is extraordinarily vulnerable to climate warming due to its dense population and the rapidly developed economy [33]. A majority of extreme temperature indices appear as abrupt changes since the last decades, with the main cold indices changing abruptly in the 1980s and the main warm indices changing abruptly in the late 1990s and early 2000s [40]. The maximum and minimum temperatures have increased significantly at rates of 0.19 • C and 0.37 • C per decade, respectively [41].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has reported that the magnitude of the changes in extreme climate events in the Yangtze River basin is projected to increase with the increasingly warming climate [42]. These variations have exerted a considerable influence on society and the ecosystem, making climate change one of the most urgent challenges facing the YRB [40].…”
Section: Introductionmentioning
confidence: 99%